The Effectiveness of the Application of a Hybrid Working System in Times of The COVID-19 Pandemic:An Explorative Study at a State-Owned Company in Indonesia - Aan Susanto; Agus Anwar; Bambang Tri Sakti; Feriska Febrina (IJHCM (International Journal of Human Capital Management), 2022)
This study was aimed at observing the interrelations among the environment-related factors, job-related factors, employee-related factors (motivation, adaptability, commitment), and their implications on the perception of the employee’s performance in times of the COVID-19 pandemic when a Hybrid Working system was applied.